A Forgotten Cause of Allergy at ER That Is Still Difficult to Diagnose and Treat at Poor Resource Setting: Angioedema after Using Angiotensin Converting Enzyme Inhibitors for 4 Years - A. A. Nilanga Nishad; K. Arulmoly; S. A. S. Priyankara; P. K. Abeysundara (Case Reports in Immunology)
Angiotensin converting enzyme inhibitors (ACEi) are the most commonly used antihypertensives. Therefore, ACEI induced angioedema (ACEi-AE) is not uncommon. Physicians tend to miss the diagnosis whenever a patient is taking the drug for years due to misbelief of “a drug that was taken for years may not be the cause for an allergic reaction or an angioedema”. But ACEi can induce angioedema after many years of usage as well as sometimes after stopping the drug even. Most of the emergency physicians and centers are not aware of clinical diagnosis and diagnostic criteria including available diagnostic tests and more importantly the treatment options of ACEi-AE. Therefore not only the diagnosis is delayed or missing but also proper treatment options are not practiced at many emergency rooms and at wards.